The Spatial Pattern of Aphis gossypii οn Cotton - Kapatos, E. T.; Stratopoulou, E.T.; Tsitsipis, J.A.; Lycouresis, D.P.; Alexandri, M.P. (ENTOMOLOGIA HELLENICA, 1998)
The spatial distribution of Aphis gossypii (Glover) on cotton was studied by using Taylor’s power law, the negative binomial parameter k and the iδ-index of aggregation. Both k and iδ were related to density with curvilinear relationships and indicated that aggregation decreases as density increases up to densities of, approximately, two individuals per leaf. At the very high densities (more than three individuals per leaf) the calculated values of the two indices recognized a tendency for an increased aggregation again. A strong linear relationship between the log mean and the log variance of the population density was obtained confirming the wide applicability of Taylor’s power law. However, the established relationship (b=1.433) assumes, for the range of the observed densities, a continuous decrease in the degree of aggregation as density increases. It is suggested that the changes in the degree of aggregation throughout the season and in relation to density are related to natural mortality.